2014
DOI: 10.18870/hlrc.v4i4.222
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Design and Facilitation Approaches that Promote Critical Thinking in Asynchronous Online Discussions: A Review of the Literature

Abstract: Asynchronous online discussions (AODs) are often used to promote critical thinking in online courses; however, recent research suggests that levels of critical thinking in discussions remain low. Furthermore, there is a lack of consensus in the literature about the definition of critical thinking and many of the existing studies focus on one specific cognitive construct. Therefore, it is unknown which instructional approaches have the strongest empirical support for promoting critical thinking across multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…Although existing research has identified numerous strategies for scaffolding online tutoring (Guo et al, 2014;Lentell, 2003;Schindler & Burkholder, 2014) This study also supports the claim that adaptive scaffolding is better than fixed scaffolding (Azevedo, Cromley, Moos, Greence, & Winters, 2011;Azevedo et al, 2004;Feng, 2012). Also, tutors should keep a close eye on the learning process and adjust their scaffolding as and when the situation demands such adjustments.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Although existing research has identified numerous strategies for scaffolding online tutoring (Guo et al, 2014;Lentell, 2003;Schindler & Burkholder, 2014) This study also supports the claim that adaptive scaffolding is better than fixed scaffolding (Azevedo, Cromley, Moos, Greence, & Winters, 2011;Azevedo et al, 2004;Feng, 2012). Also, tutors should keep a close eye on the learning process and adjust their scaffolding as and when the situation demands such adjustments.…”
Section: Resultssupporting
confidence: 77%
“…Table 10 shows that some typical strategies are considered most effective for the development of teaching presence, such as presenting learning tasks in a structured way, questioning, guiding, and summarizing. The interview data also shows that students were most impressed by and satisfied with strategies for guiding, questioning, timely feedback, and providing summaries, a result which is consistent with existing evidence on the impacts of online tutoring strategies (Guo, Gilbert, Jackman, Starns, Hagge, Faidley, & Amin-Naseri, 2014;Schindler & Burkholder, 2014). (Figure 4), which validates the role of scaffolding in supporting the development of cognitive presence.…”
Section: Scaffolds For Teaching Presencesupporting
confidence: 84%
See 2 more Smart Citations
“…The most common form of assessment has been that of grading the discussion contributions (Dennen, 2008), but it is unclear whether this form of assessment is essential for successful learning outcomes (Richardson & Ice, 2010;Schindler & Burkholder, 2014;Wee & Abrizah, 2011). This paper describes a study comparing the effect on student critical thinking of two approaches to AOD assessment: using a post-AOD assessment (a piece of work submitted after the completion of the AOD that builds on the AOD contributions), and assessing the discussion contributions themselves.…”
Section: Introductionmentioning
confidence: 99%